2021
DOI: 10.3390/biomedicines9081011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treadmill Exercise on Neural Mitochondrial Functions in Parkinson’s Disease: A Systematic Review of Animal Studies

Abstract: This systematic review sought to determine the effects of treadmill exercise on the neural mitochondrial respiratory deficiency and neural mitochondrial quality-control dysregulation in Parkinson’s disease. PubMed, Web of Science, and EMBASE databases were searched through March 2020. The English-published animal studies that mentioned the effects of treadmill exercise on neural mitochondria in Parkinson’s disease were included. The CAMARADES checklist was used to assess the methodological quality of the studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Various proteins of mitochondrial biogenesis have been found to be increased after exercise. A systematic review showed that physical exercise increased the expression levels of PGC-1α, NRF-1, NRF-2, and TFAM and promoted mitochondrial biogenesis in Parkinson’s disease ( Nhu et al, 2021 ). In addition, Zhang and Gao (2021) found that physical exercise protects against cardiovascular disease by promoting mitochondrial biogenesis.…”
Section: Molecular Mechanisms Of Physical Exercise In Sepsis Treatmentmentioning
confidence: 99%
“…Various proteins of mitochondrial biogenesis have been found to be increased after exercise. A systematic review showed that physical exercise increased the expression levels of PGC-1α, NRF-1, NRF-2, and TFAM and promoted mitochondrial biogenesis in Parkinson’s disease ( Nhu et al, 2021 ). In addition, Zhang and Gao (2021) found that physical exercise protects against cardiovascular disease by promoting mitochondrial biogenesis.…”
Section: Molecular Mechanisms Of Physical Exercise In Sepsis Treatmentmentioning
confidence: 99%
“…Various methods for treating Parkinson's disease have been studied including physical therapy, speech therapy, psychotherapy, and medication. In addition, a new trend in physical therapy is treadmill exercise, which is still being studied and has not been applied in humans yet [7]. However, medication is still the major way to enhance the symptoms of Parkinson's patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the pathological process of cognitive disorders, neuronal mitochondrial dysfunction often occurs [ 28 ], leading to excessive oxidative stress and energy deficiency in brain tissue. Exercise has been demonstrated to play an important role in improving the stability of neuronal mitochondria [ 29 , 30 ]. Moreover, exercise can induce skeletal muscle production of myokines into the blood [ 31 ], some of which promote expression of BDNF in hippocampus and inhibit production of inflammatory factors [ 32 ].…”
Section: Introductionmentioning
confidence: 99%